Research Trends in Governance, Risk and Compliance (GRC): A Scopus-Based Bibliometric Analysis Using Biblioshiny (2020–2026) - Kalmet Nehru; Fitriana Dachlan; Rachmat Agus Santoso (Manunggal Halim Jaya, 2027)
This study examines the development of Governance, Risk and Compliance (GRC) research in the fields of finance and accounting during the 2020–2026 period using a bibliometric approach. The study analyzed metadata from 464 Scopus-indexed journal articles retrieved through a systematic search and screening process. Bibliometric analysis was conducted using Biblioshiny integrated with the Bibliometrix package in R to examine publication trends, influential publications, conceptual structures, thematic development, and emerging research topics. The findings reveal a substantial increase in GRC-related publications, particularly during 2025–2026, indicating growing academic interest in integrated governance, risk management, and compliance. The most influential studies were associated with corporate governance, enterprise risk management, sustainability, and digital governance, while conceptual mapping demonstrated strong interrelationships among governance, compliance, sustainability, and information systems. Trend analysis further identified artificial intelligence, ESG performance, and sustainability reporting as emerging research themes that are expected to shape future GRC research. This study contributes to the bibliometric literature by providing a comprehensive scientific mapping of GRC research and offers practical insights for researchers, practitioners, regulators, and policymakers in identifying future research directions and strengthening governance, risk management, and compliance strategies.